Cloning and identification of the Escherichia coli murB DNA sequence, which encodes UDP-N-acetylenolpyruvoylglucosamine reductase. - Pucci, M J (1992)
The murB gene, which complemented the UDP-N-acetylenolpyruvoylglucosamine reductase (EC 1.1.1.158) mutation in Escherichia coli ST5, was cloned from an E. coli chromosomal library. murB was subcloned on a 2.8-kb PvuII fragment into pUC19 and sequenced. A 1,029-bp open reading frame encoded a 342-amino-acid polypeptide of 37,859 Da. A DNA sequence homology search revealed that murB had almost 100% homology with a previously reported unidentified open reading frame, ORFII, at 89.9 min. Physical and genetic mapping results were consistent with this map position, and minicell analyses of murB subclones showed a plasmid-encoded protein of approximately 37,000 Da, which closely matched the calculated size of the murB protein.